Boldness, Dominance, and Territoriality in the Color Polymorphic Tree Lizard, Urosaurus ornatus. (16th September 2016) - Taylor, Julie N.; Lattanzio, Matthew S.
Abstract: Social dynamics in territorial species often reflect underlying variation in aggression and other aspects of social dominance among individuals. In ornate tree lizards ( Urosaurus ornatus ), males differing in dewlap color differ in social dominance: while blue males are the dominant, aggressive morph and always territorial, yellow males tend to exhibit a less‐aggressive satellite behavioral tactic. However, in habitats with fewer available territorial resources, yellow males defend territories and increase in relative abundance. These observations suggest that consideration of social dominance alone may be insufficient to explain U. ornatus' territorial dynamics in the wild. Here, we tested how both dominance and another important behavioral trait, boldness, contribute to the outcome of territorial disputes in tree lizards. We recorded the territorial behavior of blue and yellow male tree lizards (entered in pairs) in an experimental arena. At the end of each trial, we then approached each male and recorded whether it fled (shy) or not (bold) in response to our approach. As expected, dominant blue males exploited the higher quality perch more often than yellow males. However, when approached by a simulated predator, blue males were more likely to flee than yellow males. Thus, while blue males are more dominant, yellow is likely the bolder morph. As a result, this morph may be better equipped to defend territories in riskier environments. We conclude that although dominance asymmetries may predictably drive initial territorial interactions among competing males, variation in other behaviors (like boldness) may perturb the long‐term outcome of these interactions across variable environments.